The Investigation of Self-Regulated Learning Practices During Undergraduate Skripsi Completion - Maulana, Ridwan; Nuruddin Hidayat, Didin; Sufyan, Agus (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
This study investigated the self-regulated learning (SRL) practices of undergraduate students during their Skripsi completion in the English Education Department. A quantitative survey design was employed, involving 64 students who were actively engaged in their Skripsi. Data were collected through a closed-ended questionnaire and analyzed using descriptive statistics through JASP software. The results revealed that the “Resources Management” and “Motivational Components” were the most frequently utilized SRL strategies, while “Cognitive Components” ranked the lowest, indicating potential areas for improvement. Self-regulated learning strategies such as “Evaluation” and “Set Self-Consequences” were predominant, emphasizing reflection and goal-setting, while “Organizing and Transforming,” “Keeping Records and Monitoring,” and “Seeking Assistance from the Academic Community” were less frequently utilized, suggesting a need for enhanced organizational and collaborative skills. These findings contribute to the understanding of SRL practices and offer implications for educators to leverage student success in academic achievement.